1996
DOI: 10.1111/j.1398-9995.1996.tb00091.x
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of two structured treatment and teaching programs on asthma

Abstract: The aims of the present study were as follows: 1) to evaluate the medical outcomes of two treatment and educational asthma programs 2) to determine by cost-analysis both cost and economic outcome of the programs 3) to perform a cost-benefit analysis (determining the net cost-benefit) and a cost-effectiveness analysis (determining the cost per unit of effect and the incremental cost-effectiveness ratio) from the perspective of health program policy makers (HPP; indirect costs, i.e., loss of productivity, exclud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…Cost-effectiveness analysis has been the most common form of economic evaluation used to evaluate health promotion programmes [17]. Intermediate outcomes such as behaviour change, changes in knowledge, attitudes, and practice [18]; health service utilisation or preference for treatment options [19,20]; or the level of participation in treatment decision-making [21], are often used. This limits the comparability of cost-effectiveness results from health promotion programmes with that of other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…Cost-effectiveness analysis has been the most common form of economic evaluation used to evaluate health promotion programmes [17]. Intermediate outcomes such as behaviour change, changes in knowledge, attitudes, and practice [18]; health service utilisation or preference for treatment options [19,20]; or the level of participation in treatment decision-making [21], are often used. This limits the comparability of cost-effectiveness results from health promotion programmes with that of other interventions.…”
Section: Introductionmentioning
confidence: 99%
“…After excluding duplicates, letters, editorials, and reviews and classifying by medical condition on the basis of the title, there were a total of 2,121 candidate practice guidelines and 2,377 candidate economic analyses. The medical conditions with the most candidate practice guidelines and at least 10 candidate economic analyses for each category were acute myocardial infarction, 21–56 asthma, 57–90 smoking cessation, 91–113 colorectal cancer, 114–140 and breast cancer. 141–166 The second literature search with the addition of each condition's MESH heading resulted in the identification of additional guidelines and economic analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the studies originated from the United States of America7,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54, followed by Europe8,55,56,57,58,59,60,61,62,63,64,65,66,67, Asia68-72, and Australia 73,7475,76. There was one economic evaluation concerning enhanced asthma management30 done in 1991, and at least one between 1994 and 2012.…”
Section: Background Of Reviewed Studiesmentioning
confidence: 99%
“…There were 5 CBA studies that reported a positive net benefit for every dollar spent 35,60,62,63,66. In addition to the excluded non-full CBA study29, there was another study that also did not value the health outcomes in monetary units 40.…”
Section: Background Of Reviewed Studiesmentioning
confidence: 99%
See 1 more Smart Citation